URGENSI PROGRAM PARENTING BAGI ORANG TUA ANAK USIA DINI (Studi Deskriptif Pada TK IT Permata Sunnah Banda Aceh) - Ismiati Ismiati (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2021)
This study aims to determine the response of parents to the importance of implementing parenting programs at the Early Childhood Education Institution (PAUD). The problem that often occurs is the frequent occurrence of asynchronous between the patterns of education received by early childhood in the education and care process between PAUD or TK and their families. Differences in education patterns between teachers and parents in how to educate early childhood sometimes make it difficult to change behavior for the better in early childhood, this is because there are differences in understanding between teachers and parents about early childhood education. With the parenting program, it is hoped that it can bridge and eliminate differences in perspectives and the education and care system between parents of children and teachers. However, children will spend more time with their parents than their teachers at school. This research is descriptive qualitative by interviewing 20 parents who send their children to TK IT Permata Sunnah Banda Aceh. The results showed that the parents of the early childhood interviewed considered the parenting program very important, in fact they were very supportive of the activity. Parents recommend that schools conduct parenting programs, especially in the form of seminars, social gatherings and various other forms of educational activities to broaden the knowledge of parents in caring for early childhood.